Need-supporting gamification in education: An assessment of motivational effects over time. (December 2018) - van Roy, Rob; Zaman, Bieke
Abstract: Although many studies have focused on the potential of implementing gamification in education, the existing literature remains inconclusive about its effectiveness. In order to make sense of the contradictory findings regarding the effectiveness of implementing game design elements in an online learning environment, this paper complements the available body of research by addressing three holes. We have (1) analysed gamification's underlying motivational processes from a Self-Determination Theory-perspective, thereby accounting for the motivational effects of various game design implementations; (2) empirically assessed subtle motivational changes over time, and (3) accounted for the potential individual differences in motivational effects of gamification. Over a period of 15 weeks, we administered four surveys to measure the possible evolution in students' ( N =  40) motivational levels in response to interacting with need-supporting game elements that were implemented in Google + Communities used in a university course. Participants' autonomous and controlled motivation was curve linear, showing an initial downward trend that surprisingly shifted to an upward tendency towards the end of the semester. Their controlled motivation stayed stable throughout. The results illustrated the significance of the individual nature of motivational processes, the importance of sensitive longitudinal motivation measurements, and the relevance of the implemented game elements' design characteristics. We end this article by opening the debate on using theoretical lenses when designing gamification, and by providing avenues for future research. Highlights: Providing theoretical lenses to research and design gamification. Showing game elements' affordances as impacting gamification's motivational effects. Illustrating the benefits of using a long-term systematic exploration of motivation. The motivational impact of gamification is person-specific. No evidence is found for a novelty effect of gamification.